Men’s and women’s egocentric and allocentric knowledge: The involvement of mental rotation ability and spatial beliefs - Miola, Laura; Muffato, Veronica; Pazzaglia, Francesca; Meneghetti, Chiara (Frontiers in Psychology, 2023)
Individual factors can play a relevant role in explaining gender differences in environmental learning in terms of visuospatial abilities and beliefs about spatial abilities, such as stereotypes and growth mindset about navigation ability. In this study, we aim to investigate how mental rotation ability and spatial beliefs interact in the acquisition of egocentric and allocentric spatial knowledge. A sample of 244 participants (140 women) completed individual difference measures, including a mental rotation test (MRT) and questionnaires on gender stereotypes and growth mindsets about navigation ability. Participants then learned a specific route in a virtual environment and performed an egocentric pointing task and an allocentric pointing task. Men performed better in mental rotation and egocentric pointing tasks. Moreover, mental rotation ability predicted both egocentric and allocentric pointing performance; growth mindset predicted allocentric pointing. In general, these results suggest that, despite gender differences in some spatial measures, cognitive abilities and beliefs contribute to supporting environmental knowledge in both men and women.